Influence of Coarse Aggregate Gradation on the Mechnical Properties of Concrete, Part II: No-Fines Vs. Ordinary Concrete - Buller, A. S.; Tunio, Z. A.; Abro, F. U. R.; Ali, T.; Jamali, K. A. (Engineering, Technology & Applied Science Research, 2019)
This study aims to investigate the effect of different gradations of coarse aggregates on mechanical properties of no-fines concrete (NFC). NFC reduces a structure’s self-weight, thus minimizing cost. The effects of coarse aggregate gradation on mechanical properties such as compressive strength, split tensile strength, and flexural strength were studied and compared at the end of 28-day water curing. A fixed cement- to-aggregate proportion 1:6 with 0.5 water/cement (w/c) ratio was adopted. Four gradations of coarse aggregates ranging between specific maximum and minimum size were used, namely 5mm-4mm, 10mm-4mm, 20mm-4mm and 20mm-15mm. The results of this study reveal the substantial effect of the gradation of coarse aggregates on strength properties compressive and tensile strength of NFC.